BS32 The role of branched-chain keto acids in mediating insulin resistance in the failing heart. (4th June 2021) - Karwi, Qutuba; Wagg, Cory; Zhang, Liyan; Ussher, John; Lopaschuk, Gary
Abstract : Brief introduction: Perturbed branched-chain amino acids (BCAA) oxidation positively correlates with the severity of cardiac insulin resistance in heart failure. We previously demonstrated that cardiac-specific deletion of the BCAA oxidative enzyme mitochondrial branched-chain aminotransferase (BCATm) increases cardiac BCAA levels and decreases branched-chain keto acids (BCKA) levels, enhances insulin-stimulated cardiac glucose oxidation rates. This increased cardiac insulin sensitivity is associated with an increase in the phosphorylation of protein kinase B (Akt) and activation of pyruvate dehydrogenase (PDH), the rate-limiting enzyme of glucose oxidation. However, whether it is the accumulation of BCAA or BCKA that is critical in mediating cardiac insulin resistance is unknown. How perturbed BCAA oxidation may mediate cardiac insulin resistance in heart failure is also unknown. Explanation of basic Methods: To address these questions, we first examined the effects of selectively enhancing cardiac BCKA levels on cardiac insulin-stimulated glucose oxidation. We perfused isolated working mice hearts (male and female C57BL/6N, n=8-10) with high levels of BCKA (α-keto-isocaproate 80 μM, α-keto-β-methylvalorate 100μM, α-keto-isovalerate 70 μM), levels that can be seen in diabetes and obesity. Results: High levels of BCKA completely blunted insulin-stimulated glucose oxidation rates and increased fatty acid oxidation rates. We also found that BCKA abolished insulin-stimulated mitochondrial Akt, an effect that was associated with PDH deactivation. We next determined the potential protective effect of reducing cardiac BCKA levels in the failing heart. We randomized WTCre+/+ and cardiac-specific BCATm-/- mice (male, 25-30g, n=6-8) to undergo either sham surgery or transverse aortic constriction surgery to induce heart failure. Five weeks post-surgery, there was a marked increase in insulin-stimulated glucose oxidation rates in the BCATm-/- failing hearts compared to the WTCre+/+ failing hearts, with no significant effect on glycolysis rates. Enhanced cardiac insulin sensitivity was associated with a significant decrease in fatty acid oxidation rates in the BCATm-/- failing hearts compared to the WTCre+/+ failing hearts. This decrease in fatty acid oxidation in the BCATm-/- failing hearts was associated with a significant decrease in myocardial oxygen consumption rates. As a result, cardiac efficiency (cardiac work/myocardial oxygen consumption) was significantly increased in the BCATm-/- failing hearts compared to the WTCre+/+ failing hearts. Conclusions/implications: We conclude that the accumulation of BCKA, and not BCAA, is a major contributor to cardiac insulin resistance via abrogating mitochondrial translocation of Akt. Targeting BCKA may represent a potential therapeutic approach to improve cardiac insulin-stimulated glucose oxidation in the setting of heart failure, obesity and diabetes. Conflict of Interest: None